Case Report: Efgartigimod demonstrates significant clinical efficacy in double seropositive myasthenia gravis: a case report of a rare variant and analysis of pathomechanisms - Huang, Xiaohui; Wan, Yue; Chen, Yu; Lei, Keqi (Frontiers in Immunology, 2025)
Double Seropositive Myasthenia Gravis (DSP-MG), a rare variant of Myasthenia Gravis (MG), is defined by the simultaneous presence of both anti-acetylcholine receptor (AChR) antibodies and anti-muscle-specific tyrosine kinase (MuSK) antibodies in the serum of affected individuals. Currently, no standardized therapeutic protocol exists for DSP-MG due to its scarcity and clinical heterogeneity. Herein, we report a case of a 68-year-old female patient with DSP-MG who showed significant clinical improvement during an acute exacerbation after treatment with the FcRn antagonist efgartigimod, following the failure of conventional therapy. After a cycle of efgartigimod treatment, complete resolution of myasthenic symptoms was observed. During the 6-month follow-up, with sustained clinical remission and attainment of Minimal Manifestation Status (MMS). This case represents the first documented use of efgartigimod in a DSP-MG patient, providing preliminary clinical evidence for its potential efficacy in this rare and poorly understood subtype. Our findings contribute to the limited literature on DSP-MG and suggest that FcRn inhibition may offer a viable treatment option where conventional therapies fail. Efgartigimod may represent a potential therapeutic agent for DSP-MG.